Changes of phospholipids during the lipid peroxidation in workers exposed to coal-rock dust - Ibraev, S.A.; Koigeldinova, Sh.S.; Andybaeva, A.E.; Talaspayeva, A.; Krasikova, K.A. (Fundamental and Experimental Biology, 2016)
The article presents the results of a study of lipid peroxidation when exposed to coal-rock dust on the organism of miners depending on length of service and in experimental animals. It was found that fairly significant change in the fractional composition of phospholipids inthe blood of miners there after having worked for more than 15 years and is dependent on the activation of lipid peroxidation. In experimental animal studies, a decrease of phosphatidylcholine and phospholipids of the inner side of the cytoplasmic membrane — phosphatidylinositol and phosphatidylserine, phosphatidyl — ethanolamine may be indicative of increasing the permeability of the plasma membrane in the conditions of formation of fibrosis.